Bimbingan Teknis Pembuatan Sabun Cuci Piring Menggunakan Bahan Dasar Limbah Kulit Pisang dan Pembuatan Virgin Coconut Oil dengan Metode Sederhana - Ahmad Yani; Yano Hurung Anoi; Eko Armiyanto; Dedy Daud; Syahrul Mubaraq; Dimas Ifnu Pratama; Adelia Zepty Azzahra (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2022)
Banana peels contain saponins (producing foam), flavonids and tannins (antiseptics) which can be used as the main raw material in making soap and orange peels which have a nice and fresh aroma can be used as additives for soap making. Meanwhile, Virgin Coconut Oil (VCO) is the result of processing coconuts into pure coconut oil which produces a product in the form of oil that is clear in color, has a distinctive coconut smell, and has very low water content, and lasts more than one year if stored. VCO is made using traditional methods without the addition of chemicals. VCO has a significant role for the body, including being able to get rid of fat, can reduce or prevent blood clots, minimize cholesterol, produce oxidants in cells, and can prevent cancer and heart disease. The purpose of this community service is to provide understanding and training in making dish soap using banana peel as the basic ingredient and making VCO traditionally for residents of the Bontang Kuala sub-district, Bontang City. The method of implementing community service activities (PkM) is carried out using socialization methods, demonstrations and direct practice carried out by residents of the Bontang Kuala sub-district. The results of this community service provided extraordinary benefits to the women of the Bontang Kuala sub-district because they did not know the various benefits of banana peel waste for making dish soap and the benefits of VCO for health and did not know how to make dish soap from banana peel waste and the manufacturing process. VCO with simple technology using household appliances at home. Keywords: BIMTEK, manufacturing, liquid soap, banana peel, and VCO.